PENGUATAN INSTRUMEN PERLINDUNGAN HAM DALAM PEMBAHARUAN KUHAP UNTUK MEWUJUDKAN CITA NEGARA HUKUM - Bambang Santoso; Muhammad Rustamaji; Itok Dwi Kurniawan (Universitas Suryakancana, 2023)
According to the 1945 Constitution, Indonesia is a state of law.Â Law violation must be prosecuted according to the rules of applicable law. Violation of criminal law, its enforcement through criminal procedural procedures. Criminal Procedure Code needs to be updated because of its many weaknesses. Criminal Procedure Code reform must guarantee the achievement of the ideals of a rule of law state. This study aims to reveal a model for strengthening human rights protection instruments in the reform of the Criminal Procedure Code. This research is a normative study using secondary data, in the form of primary, secondary and tertiary materials. Data collection techniques with library research. The analysis was carried out prescriptively with the deduction method. The results show that in the reform of the Criminal Procedure Code the instrument for protecting human rights is strengthened because Indonesia has ratified several international conventions, including the Covenant on Civil and Political Rights (ICCPR). The Criminal Procedure Code must comply with several ICCPR provisions, including regarding detention by investigators as short as possible and immediately brought before the judge, stipulating the right to remain silent as an embodiment of the principle of non-self-incrimination.Â Keywords: Criminal Procedure Code Reform, Human Rights Protection, Rule of Law.